Preharvest Natural Multitoxin Contamination of Winter Wheat Genotypes in Hungary with Special Attention to Aflatoxins and HT-2 Toxin - Berényi Attila; Szabó Balázs; Meszlényi Tamás; Vágvölgyi Csaba; Tóth Beáta; Mesterházy Ákos (2024)
Toxigenic fungi are among the most significant disease-causing agents in wheat. DON is the most common Fusarium mycotoxin, and for a long time, it was the only toxin researched. However, multitoxin data from wheat samples have drawn attention to the fact that much more toxins can be involved in the wheat toxin story than we supposed earlier. For resistance breeding, we need a more detailed approach to identify toxins that occur above the limit and identify the source of the fungal species that produces them. This study analyzed local wheat varieties for fungal infections and natural multitoxin contamination. Eighteen winter wheat genotypes were tested for fungal contaminations across three different locations in 2021 and 2022. Fourteen different mycotoxins—deoxynivalenol, aflatoxins (B1, B2, G1, and G2), fumonisins (B1 and B2), sterigmatocystin, ochratoxin A, zearalenone, T-2, HT-2, and diacetoxyscirpenol—were analyzed using HPLC/triple-quad MS. Toxigenic species such as Fusarium, Aspergillus, and Penicillium had low rates of occurrence, but the toxin contamination was often surprisingly high. Many samples without corresponding fungal infections were also identified as containing mycotoxins. Therefore, the identified fungal infection is less useful for forecasting toxin level. In conclusion, mycotoxin contamination is decisive. Most samples were contaminated by one or more mycotoxins. Although the mycotoxin concentrations typically remained below EU limits, some samples exhibited higher levels, particularly aflatoxins and Ht-2 toxin. Significant variations were observed across year, location, and genotype. For several toxins, significant genotype differences were identified, supporting the hypothesis that resistance may be a useful and suitable control measure. Stability of toxin contamination across years and locations is a very valuable trait; genotypes were identified with low toxin levels and stability (low variance) to all mycotoxins tested. It seems that, in addition to DON, more attention should be given to aflatoxin B1, B2, and G1, which provided similar concentrations. The HT-2 toxin was present in many samples surpassing EU limits. This is the first report on the dangerous occurrence of preharvest-origin aflatoxins and the HT-2 toxin of wheat in Hungary.
Keywords: Biológiai tudományok